The UV/optical spectra of the Type Ia supernova SN 2010jn: a bright supernova with outer layers rich in iron-group elements - Hachinger, S; Mazzali, P; Sullivan, M; Ellis, R; Maguire, K; Gal-Yam, A; Howell, D; Nugent, P; Baron, E; Cooke, J; Arcavi, I; Bersier, D; et al. (2013)
Radiative transfer studies of Type Ia supernovae (SNe Ia) hold the promise of constraining both the density profile of the SN ejecta and its stratification by element abundance which, in turn, may discriminate between different explosion mechanisms and progenitor classes. Here we analyse the Type Ia SN 2010jn (PTF10ygu) in detail, presenting and evaluating near-ultraviolet (near-UV) spectra from the Hubble Space Telescope and ground-based optical spectra and light curves. SN 2010jn was discovered by the Palomar Transient Factory (PTF) 15 d before maximum light, allowing us to secure a time series of four near-UV spectra at epochs from -10.5 to +4.8 d relative to B-band maximum. The photospheric near-UV spectra are excellent diagnostics of the iron-group abundances in the outer layers of the ejecta, particularly those at very early times. Using the method of 'Abundance Tomography' we derive iron-group abundances in SN 2010jn with a precision better than in any previously studied SN Ia. Optimum fits to the data can be obtained if burned material is present even at high velocities, including significant mass fractions of iron-group elements. This is consistent with the slow decline rate (or high 'stretch') of the light curve of SN 2010jn, and consistent with the results of delayed-detonation models. Early-phase UV spectra and detailed time-dependent series of further SNe Ia offer a promising probe of the nature of the SN Ia mechanism. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.